The Effects of Brain-Based Teaching With I-Think Maps and Brain Gym Approach towards Physics Understanding (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2019)
The purpose of this study was to assess the effects of Brain-Based Teaching with i-Think Maps and the Brain Gym Approach (BBT-iTBA) compared to the conventional teaching approach (CTA) towards Physics’ conceptual understanding amongst male and female matriculation students in the north of Peninsular Malaysia. 180 students (83 were male and 97 were female), aged around 19 years old, from two Matriculation Colleges, were involved as research sample for the targeted population. The effects of the BBT-iTBA compared to the CTA towards Physics’ conceptual understanding amongst students were determined using a quasi-experimental non-equivalent group design, involving an experimental group of students (exposed to BBT-iTBA) and a control group of students (received CTA). Data gathered from the Physics Conceptual Understanding Test (PCUT), administered on the sample before and after the intervention of both teaching approaches, were then analyzed statistically. The two way ANOVA analysis results indicated that after the intervention, students’ Physics conceptual understanding differ significantly due to the implementation of the different teaching approaches, with a great size effect. Students who were exposed to BBT-iTBA performed significantly better in the PCUT than students who received CTA. Although gender alone did not affect students’ Physics conceptual understanding, the results obtained revealed that the effects of the interaction between the implementation of the teaching approaches and gender on the attainment of students’ Physics conceptual understanding were significant, with a simple size effect. The main features of the BBT-iTBA, which are: focusing on the optimum function of the brain; promoting and enhancing the skills of thinking; and creating a relaxed and fun learning environment; are found to be the significant triggers for students to better understand Physics conceptually and excel in the subject.